Технології лиття та приготування алюмінієвих сплавів за допомогою засобів магнітної гідродинаміки - Фікссен, В.М.; Карпухін, Є.О. (Physico-technological Institute of Metals and Alloys, 2024)
This article presents some developments of the Physico-technological Institute of Metals and Alloys of the National Academy of Sciences of Ukraine related to the technologies of aluminum alloys, which have been successfully tested in laboratory and production facilities. Applied magnetohydrodynamics in metallurgy and foundry manufacturing has technological opportunities that are either unattainable or difficult to implement when other physical principles are used. Progress in this area has been slow due to the fact that large non-magnetic gaps are inevitable in metallurgical devices used in metallurgy and foundry. However, due to the improvement of refractory and electro-technical materials, the use of magnetohydrodynamics in metallurgical production of the world is constantly increasing. The following technological developments are described. Casting under electromagnetic pressure according to the low-pressure casting scheme, in which the pressure of the compressed gas is replaced by electromagnetic influence. As a result, there is no need to seal the crucible with liquid metal and the accuracy of the preset filling mode of the mold is increased. Casting under electromagnetic pressure with a dispersed gating and feeding system. With this casting method, a high liquid metal utilization rate is achieved, which is unachievable in other casting methods, and the absence of shrinkage defects is ensured. Electromagnetic stirrer for pulsating effect on liquid metal, which is an alternative to the electromagnetic mixer of traveling magnetic field. Complex refining of aluminum alloys, including filtration of the melt through a ceramic foam filter and its simultaneous purging with argon. Increased efficiency is achieved by application of electromagnetic factors.